2020
DOI: 10.1016/j.compositesa.2020.105806
|View full text |Cite
|
Sign up to set email alerts
|

New tool for reduction of harmful particulate dispersion and to improve machining quality when trimming carbon/epoxy composites

Abstract: Conventional machining of carbon fiber reinforced plastic composites (CFRPs) generates minute chips that get suspended in air causing a hazard compromising operator safety. This study investigates the influence of cutting parameters (feed speed, cutting speed, radial depth of cut, tool geometry and tool wear) during trimming of CFRP on the form and quantity of harmful particles dispersed. Also, performance of two classical PCD tool geometries (two straight flutes, two helix flutes) have been compared with newl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 20 publications
0
21
0
Order By: Relevance
“…All materials have been edge trimmed using a full slot up/conventional milling procedure with a diamond coated burr style tool (OSG Corporation, UK). Nguyen-Dinh et al 12 show that increased radial depth of cut increases the surface damage and depth of damage, and the use of full slotting is likely to provide high levels of damage. The DIA-BNC tool is a fine nicked router designed for CFRP trimming with the nick and flute form designed to eliminate uncut fibres and delamination.…”
Section: Verification Of Methodsmentioning
confidence: 99%
“…All materials have been edge trimmed using a full slot up/conventional milling procedure with a diamond coated burr style tool (OSG Corporation, UK). Nguyen-Dinh et al 12 show that increased radial depth of cut increases the surface damage and depth of damage, and the use of full slotting is likely to provide high levels of damage. The DIA-BNC tool is a fine nicked router designed for CFRP trimming with the nick and flute form designed to eliminate uncut fibres and delamination.…”
Section: Verification Of Methodsmentioning
confidence: 99%
“…The test results indicate that the trimming with a mixture of lower cutting speed and higher feed speed can reduce the harmful effects. 17 It has been noted that machine extension does not directly correspond to specimen strain. However, there is a correlation between them.…”
Section: Mechanical Testing On Edge Treated Compositesmentioning
confidence: 99%
“…The results indicate that the trimming with a mixture of lower cutting speed and higher feed speed can reduce the harmful effects. 17 A new study indicated that the cutting force and sub-surface damage were increased with increasing fiber orientations. 18 At the same time, the rake angle had no or minimal effects on the cutting forces and the observed damage.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the variety of cutting tools used in machining of composites are: high-speed steel (HSS), tungsten carbide, cubic boron nitride (cBN) and polycrystalline diamond (PCD). In the case of composites, apart from the tool material itself, the processing parameters are also very important [ 26 ].…”
Section: Introductionmentioning
confidence: 99%